THE IMAGE OF GENDER CONSTRUCTIONS IN BEVERAGE BRANDS ADVERTISEMENT - YARRA FAHIRATUNNISA; AMRIN SARAGIH (LINGUISTICA, 2022)
This study aims to construct gender in Indonesian beverage advertising products based on Sara Mills' critical discourse analysis theory through the discourse displayed. This research was conducted with a qualitative method. Where, the source of data in this study was taken from the visual and contextual in the advertisements. These ads come from mineral water namely Aqua and Vit brands. The adverts were taken from the brands' official YouTube channel, which consisted of 8 ad videos. The results of this study indicate that there are findings of the subject, object, and viewer position in accordance with Sara Mills' theory. This research also shows how the forms of gender construction that lead to gender discrimination, injustice and patriarchy that are accepted by women themselves are displayed in the advertisement